1995
DOI: 10.1111/j.1151-2916.1995.tb08068.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dispersion Frequency of Hot‐Pressed Z‐Type Magnetoplumbite Ferrite with the Composition 2CoO·3Ba0.5Sr0.5O·10.8Fe2O3

Abstract: The high‐frequency magnetic properties of strontium‐partially‐substituted Z‐type magnetoplumbite with the composition 2CoO·3Ba1‐x.SrxO.yFe2O3 were studied using a hot‐pressing technique. The best properties were obtained for a sample hot‐pressed in oxygen, having x and y values of 0.5 and 10.8, respectively. The resonant frequency of that sample, corresponding to a μ” maximum reaching 2.5 GHz, was significantly larger than the value of 1.4 GHz previously reported for unsubstituted Z with the composition 2CoO·3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The preliminary studies by the present authors aimed at improving the magnetic properties of a Co 2 Z compound, detailed elsewhere. 2 This study aims at lowering the sintering temperature of the Z type hexagonal ferrite for co-firing with silver electrode * Corresponding author. to prepare chip inductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary studies by the present authors aimed at improving the magnetic properties of a Co 2 Z compound, detailed elsewhere. 2 This study aims at lowering the sintering temperature of the Z type hexagonal ferrite for co-firing with silver electrode * Corresponding author. to prepare chip inductors.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it was found effective to decrease iron content from the stoichiometric value 12 of Co 2 Z to 9.8 for lowering sintering temperature. 2 Secondly, cobalt ions were partially replaced by copper ions, and barium ions were also partially replaced by strontium and bismuth ions. This process is based on the concept of decreasing sintering temperature of the ferrite as low as possible and of increasing the permeability as high as possible, based on the results already reported 2 in our preliminary experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of iron deficiency significantly reduces the Fe 2+ ions in the sample and thereby inhibiting the electron hopping between Fe 3+ and Fe 2+ ions which causes to accelerate the sintering and densification [21]. It is the fact that the decrease iron content from the stoichiometric value effectively lowers the sintering temperature [22]. We also assume that nickel ions are partially replaced by copper ions, based on the concept of reducing the sintering temperature as low as possible and enhancing the permeability as high as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Its natural resonance frequency f r can be predicted in higher frequency while the value of permeability 0,i is still unaltered or higher. Many studies have reported that the quasi-static permeability 0,i is 8-12 and the resonance frequency is 1.5 GHz for bulk Co 2 Z [9][10][11]. In order to contrast with bulk Co 2 Z, the intrinsic quasi-static permeability 0,i and resonance frequency f r of Ce 2 Fe 17 N 3−␦ material should be known.…”
Section: Introductionmentioning
confidence: 99%